Photocatalytic dye degradation efficiency and reusability of Cu-substituted Zn-Mg spinel nanoferrites for wastewater remediation. (August 2022) - Jasrotia, Rohit; Suman,; Verma, Ankit; Verma, Ritesh; Ahmed, Jahangeer; Godara, Sachin Kumar; Kumar, Gagan; Mehtab, Amir; Ahmad, Tokeer; Kalia, Susheel
Abstract: A series of unmodified and copper-modified zinc‑magnesium nanoferrites [Zn0.7 Mg0.3-x Cux Fe2 O4 (x = 0.0, 0.02, 0.04, 0.06)] were prepared to degrade methylene blue (MB), a widely used textile dye and a threat to humans and the environment. The X-ray diffraction data reveals a spinel cube-like crystal structure with no additional phases. The sharpness and frequency of XRD peaks highlighted the nanocrystalline structure of fabricated photocatalysts. The calculated crystallite size (t) shows inconsistent behavior within 13–25 nm on doping copper ions within the crystal matrix of Zn-Mg nanoferrites. The morphological analysis showed the existence of spherical and aggregated nanoparticles for the synthesized Zn0.7 Mg0.3 Fe2 O4 (x = 0.0), and Zn0.7 Mg0.28 Cu0.02 Fe2 O4 (x = 0.02) specimens. In the fabrication of Zn0.7 Mg0.3 Fe2 O4 (ZMF1), Zn0.7 Mg0.28 Cu0.02 Fe2 O4 (ZMF2), Zn0.7 Mg0.26 Cu0.04 Fe2 O4 (ZMF3) and Zn0.7 Mg0.24 Cu0.06 Fe2 O4 (ZMF4) nanoferrites, the predicted band gaps were 2.30 eV, 2.18 eV, 2.07 eV, and 1.94 eV, respectively. The FTIR spectrum shows stretching vibrations in Fe-O complexes at the A-sites and B-sites, whereas the Raman spectrum exhibits five Raman active vibrational modes at 230–800 cm −1 . The nanophotocatalysts showed excellent magnetization values around 4.44–12.92 emu/g with an applied field of 6000 Oe. In the photocatalytic degradation of methylene blue, Zn0.7 Mg0.24 Cu0.06 Fe2 O4 (x = 0.06) nanophotocatalyst showed a maximum rate constant of 0.0252 min −1 and 90% photocatalytic degradation efficiency. The nanoferrites showed excellent photocatalytic activity for five cycles and were easily separated using an external magnet. Graphical abstract: Unlabelled Image Highlights: Synthesis of Cu-substituted Zn-Mg spinel nanoferrites Photocatalytic degradation of methylene blue using Zn-Mg nanophotocatalyst Cu-substituted Zn-Mg nanoferrite showed a maximum degradation efficiency of 90%. The prepared nanoferrites showed good photocatalytic activity for five cycles.